1989
DOI: 10.1080/03014223.1989.10422920
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand panbiogeography: Past, present, and future

Abstract: The history of panbiogeography in New Zealand leading up to the 1988 National Museum symposium on the panbiogeography of New Zealand is reviewed. The general historical significance of Leon Croizat's contribution to the natural sciences and his impact on New Zealand biogeography is discussed. It is suggested that Charles Fleming's biogeographic synthesis of New Zealand represented a major prelude to the current New Zealand interest in panbiogeography. Panbiogeography could playa major role in the contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
(40 reference statements)
0
6
0
1
Order By: Relevance
“…Panbiogeography, originally proposed by Croizat (1958, 1964) and subsequently developed by several authors (Craw, 1979, 1982, 1983, 1988a, b; Craw & Weston, 1984; Page, 1987; Craw & Page, 1988; Grehan, 1988, 1989; Morrone & Crisci, 1990, 1995; Morrone, 1992, 1993, 1996; Morrone & Lopretto, 1994; Craw et al ., 1999), is an approach that emphasizes the importance of the spatial or geographical dimension of biodiversity for an appropriate understanding of evolutionary patterns and processes. By searching for repetitive distributional patterns, a panbiogeographic analysis is intended to identify biogeographically homologous distributions, allowing the correlation of distributional patterns of unrelated taxa and leading to the recognition of ancestral biotic components.…”
Section: Introductionmentioning
confidence: 99%
“…Panbiogeography, originally proposed by Croizat (1958, 1964) and subsequently developed by several authors (Craw, 1979, 1982, 1983, 1988a, b; Craw & Weston, 1984; Page, 1987; Craw & Page, 1988; Grehan, 1988, 1989; Morrone & Crisci, 1990, 1995; Morrone, 1992, 1993, 1996; Morrone & Lopretto, 1994; Craw et al ., 1999), is an approach that emphasizes the importance of the spatial or geographical dimension of biodiversity for an appropriate understanding of evolutionary patterns and processes. By searching for repetitive distributional patterns, a panbiogeographic analysis is intended to identify biogeographically homologous distributions, allowing the correlation of distributional patterns of unrelated taxa and leading to the recognition of ancestral biotic components.…”
Section: Introductionmentioning
confidence: 99%
“…Many biotic elements have arrived quite recently in New Zealand, having independently crossed ocean gaps (Jordan, 2001; McDowall, 2002, 2004; McGlone, 2005; Waters & Craw, 2006). McGlone (2006) explored the relationship between what taxa are recently‐to‐presently arriving in New Zealand and their ecologies and propagule sizes, mentioning plants with tiny spores (bryophytes and ferns) or tiny seeds (orchids), and wetland plants with hooked, barbed or sticky seeds, as particularly vagile, arriving in New Zealand continually and exhibiting low endemism, but this is contrary to the assertions of Croizat (1964) and Grehan (1989) that distributions do not correlate with dispersibility. McGlone observed that low familial/generic endemism of some groups in the flora indicates recent arrival.…”
Section: Post‐gondwanan New Zealandmentioning
confidence: 96%
“…For others, the ultimate goal is understanding processes that are not necessarily revealed by analyses of areas of endemism. Grehan (1989, p. 519) thought that ‘vicariance biogeography… [has]… dominated the interface between systematics and biogeography in the United States and Great Britain’, but whether or not this was ever true is dubious. The global perspective is very different now, and botanists, especially, are pointing to the important role of dispersal (McGlone et al.…”
Section: Introductionmentioning
confidence: 99%
“…Terrane tectonics (Craw, 1985;Cooper, 1989;Heads, 1989;Burrett et al, 1991) are often of special interest and have been used to explain lichen distributions of taxa in Anzia, Pannaria, and Xanthoparmelia in New Zealand (Heads, 1989), and of general bipolar distributions in lichens and a wide range of other biota between the southwest and northeast Pacific (Chin et al, 1991). Recent developments of panbiogeographic theory and methods are found in Craw (1988Craw ( , 1989, Grehan (1988Grehan ( , 1989Grehan ( , 1991, Henderson (1989), and Page (1989).…”
Section: Panhiogeographymentioning
confidence: 99%